The emotional life of school-level leaders - Hauseman, Cameron (Emerald Publishing Limited, 2023)
Despite being tasked with supporting the wellbeing and emotional health of staff, students, and other members of the school community, little attention has been paid to developing the same qualities in school-level leaders. The majority of the existing academic research surrounding school-level leadership focuses on what practices and strategies leaders can engage in to supporting student outcomes. Bridging the nexus between research and practice, The Emotional Life of School-Level Leaders uses insights and interpretations derived from the disciplines of psychology and educational leadership to illustrate the rich and complex emotions inherent in school-level leaders' work. This unique resource critically investigates approaches for promoting wellbeing and effective emotional regulation strategies among both individual school-level leaders and throughout K-12 education systems. In an era characterized by high levels of attrition, burnout and stress, Hauseman proposes communal strategies and policy levels to support school-level leaders' emotional regulation and wellbeing, countering individualistic approaches to self-care that absolve Ministries/Departments of Education and school districts from their responsibilities to support school-level leaders. The Emotional Life of School-Level Leaders provides a unique perspective by offering insight into who school-level leaders are, and what they need to thrive both personally and professionally.
Includes index.
Keywords: Educational leadership -- Psychological aspects.; School administrators -- Mental health.; Stress (Psychology) -- Prevention.; Education -- Leadership.; Occupational & industrial psychology.; elektronické knihy; electronic books